Co-sharing and co-constructing transition in urban-mountain areas. Reflections between anthropology and urbanism - Porcellana, Valentina; Corrado, Federica (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2024)
The illusion that mountain territories and communities were static and historically backward compared to the plaine derives from a traditional urban vision that denies them any capacity of action and movement. Starting from the beginning of the new century, the transformation of/in different mountain territories brings important and interpretative reversals which allow us to re-interpret the idea of margin and marginality and undermine the traditional urban-rural dichotomy in favor of a sinergic urban-mountain system. In this framework, the contribution aims to restore and deepen these conceptual steps necessary to implement an effective transition of mountain territories. For this purpose, the contribution intersects disciplinary perspectives between anthropology and urban planning, thus putting to work an approach that involves continuos digressions and the ability to assume a divergent thinking, capable of producing original responses that restores the mountain dynamic of contemporaneity.